Anmeldelser - Folke Frederiksen, Bodil (Danish Yearbook of Musicology, 2003)
Review of: Maj Palmberg & Annemette Kirkegaard (eds.): Playing with Identities in Contemporary Music in Africa. Nordiska Afrikainstitutet in cooperation with The Sibelius Museum / Department of Musicology, Åbo Akademi University 2002.